2009
DOI: 10.22621/cfn.v123i3.969
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Pregnancy in Free-ranging Elk, <em>Cervus elaphus nelsoni</em>, in Michigan

Abstract: Uncertainty exists as to which factors are most closely related to probability of pregnancy in Elk (Cervus elaphus), which thresholds are key for managers who want to assess the potential productivity of free-ranging Elk herds, and whether these thresholds vary among populations. We examined relationships among pregnancy, age, and mass for 513 harvested freeranging Elk in Michigan, and compared relationships with other published models and with thresholds derived from other free-ranging and penned populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Our data were similar to body mass for yearlings reported by Dean et al (1976) during early-winter ( x ¼ 162 kg) on feed grounds in western Wyoming and for 261 yearlings sampled during early-to mid-winter in the 1990s and 2000s at Starkey Experimental Station in northeast Oregon ( x ¼ 158 kg; M. Wisdom, United States Forest Service, unpublished data). Our estimates ( x ¼ 161.9 kg) were slightly lower than the average late autumn body mass reported for yearlings ( x ¼ 177 kg) in an increasing elk population in Michigan (Piasecke et al 2009) and lower than the 220 kg reported by Blood and Lovaas (1966) for 1 yearling female in Manitoba. Dale et al (2008) also concluded that winter weather and habitat had relatively little influence on growth and subsequent body size in caribou over the next summer, and indicated that growth rates during summer were limited by summer nutrition levels.…”
Section: Other Evidence Of Summer Limitationscontrasting
confidence: 80%
See 2 more Smart Citations
“…Our data were similar to body mass for yearlings reported by Dean et al (1976) during early-winter ( x ¼ 162 kg) on feed grounds in western Wyoming and for 261 yearlings sampled during early-to mid-winter in the 1990s and 2000s at Starkey Experimental Station in northeast Oregon ( x ¼ 158 kg; M. Wisdom, United States Forest Service, unpublished data). Our estimates ( x ¼ 161.9 kg) were slightly lower than the average late autumn body mass reported for yearlings ( x ¼ 177 kg) in an increasing elk population in Michigan (Piasecke et al 2009) and lower than the 220 kg reported by Blood and Lovaas (1966) for 1 yearling female in Manitoba. Dale et al (2008) also concluded that winter weather and habitat had relatively little influence on growth and subsequent body size in caribou over the next summer, and indicated that growth rates during summer were limited by summer nutrition levels.…”
Section: Other Evidence Of Summer Limitationscontrasting
confidence: 80%
“…Estimates of nutritional condition of non‐lactating females also are confounded because no validated approach exists to identify lactation history over the previous 5–6 months before autumn capture without intensive and costly calf‐capture approaches. Therefore, females deemed non‐lactating at the time of capture are likely to be a heterogeneous group of animals in terms of their nutritional demands and expenditures over the previous months, and inferences from their condition data could be both ambiguous and potentially misleading (e.g., Piasecke et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not detect any effects of parasites, alone or in combination, on host pregnancy. While female ungulates in poor condition are less likely to conceive and carry pregnancies to term in some species ( VanRooyen, 1993; Piasecke et al, 2009 ), the effects of body condition and parasite infection on reproduction are very difficult to disentangle without experimental studies. Accordingly, other observational studies on fitness effects in ungulates have also failed to find strong evidence for a negative effect of parasites on reproductive fitness ( Irvine et al, 2006; Hughes et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age‐specific body mass of cervids is subject to temporal variation driven by fluctuations in absolute density and habitat quality, and valuable as part of a suite of herd performance metrics (Adams and Pekins , Morellet et al , Piasecke et al ). Body mass has been shown to respond to herd productivity (Gaillard et al , Schwartz and Hundertmark , Stewart et al ), juvenile survival (Loison et al , Unsworth et al , Cook et al ), and relative density (Keyser et al ).…”
mentioning
confidence: 99%